Political Parties and Policy Change in Canadian Agricultural Marketing Institutions. Issue 5 (2nd November 2021) - Skogstad, Grace
ABSTRACT: Examining issue politicization of regulated marketing in Canadian agriculture, this article investigates factors affecting political parties' strategies in response and the ensuing consequences for policy change. It argues that parties adopt a politicization strategy when doing so advances both their ideational and electoral goals. Politicization strategies of Canadian parties are also affected by territorialism's impact on their capacity to align their ideational and electoral goals. When territorialism has favored conservative political parties, they have pursued politicization strategies associated with paradigmatic reforms. When issue politicization transcends regions, national office-seeking parties have adopted depoliticization strategies associated with first- and second-order policy change.